Reconstructing late-Holocene environmental change in Iceland using high-resolution tephrochronology - Streeter, Richard Thomas; Dugmore, Andrew J. (The Holocene, 2013)
High resolution records of sediment accumulation are necessary to evaluate subtle temporal and spatial variations in sediment flux, especially in the context of decadal-scale human-environment interactions. Digital photography using consumer-grade cameras may be used to gather thousands of stratigraphic measurements to +/- 1 mm (potentially equivalent to +/- 2 years of accumulation) and provide data amenable to statistical manipulation. This new approach is illustrated with an evaluation of 15th century landscape change in Iceland. High resolution measurements show that apparent 'spikes' in accumulation after episodes of plague are an artefact of lower resolution measurements (+/- 2.5 mm) over decadal periods. Regional records show little change in sediment accumulation rates after the plagues but key local records made possible using this new methodology reveal that the period ad 1389-1416 (encompassing the plague outbreak of ad 1402) had some of the lowest sediment accumulation rates since settlement of the island. This new approach to landscape assessment indicates that in this pastoralist community the aftermath of human mortality rates of 50-60% saw no development of feral sheep populations or a switch to less labour-intensive wool production. The implication is that cattle production was maintained and the relative easing of landscape impacts could explain the lag between 14th century climatic deterioration and 18th century increases in landscape change.